Penentuan Status Mutu Air Metode Storet DAS Kali Curah Macan - Saiful Anwar; Budi Hariono; Michael Joko Wibowo; Merry Muspita Dyah Utami (Jurnal Ilmiah Inovasi, 2018)
The monitoring station of Curah Macan Watershed is located in Arjasa Village, Arjasa District, Situbondo Regency with 7o71'66 " at the South Latitude and 114o12'17" at the East Longitude. The aim research is to know the quality of water routinely, so that the water quality condition of river water body can be detected from the beginning. This is due to changes in land functions that have reduced water absorption function, erosion, sedimentation and industrial and household activities. Therefore, research on the analysis of the status of water quality especially in the Curah Macan watershed is very important to be done periodically in order to maintain its sustainability. The research using STORET method shows the water quality of Curah Macan watershed in the period of January - December 2017 for the quality of class I, II, III and IV has a score respectively -50; -28; -12 and -4 so that the water quality qualification is bad, moderate, moderate and good.Â Keyword : Kali Macan Watershed, Storet Method, Water Quality, Period January - December 2017